THE EFFECT OF SERVICE QUALITY, CORPORATE IMAGE, CUSTOMER SATISFACTION AND SWITCHING BARRIER ON CUSTOMER LOYALTY (The Insurance Company Case Study) - Muhammad Okidarsyah (Jurnal Teknobisnis, 2012)
The modern competitive industry today, loyal customer is one of the important issues for company to survive. They have to maintain a loyal customer due to increasingly cost of acquiring new customer; moreover there is a positive relationship between customer loyalty and company profits. In order to create customer loyalty, the company needs to consider about the factor influence loyalty. The aim of the study was to examine of those factors are influence customer loyalty in insurance industry. The research uses Structural Equation Modeling (SEM), data are obtained from customer XYZ Jember and Banyuwangi branch office that have been a customer of at least 1 (one) year. From the analysis of customer loyalty, it is significantly influenced by the quality of service and customer satisfaction. In addition it also concluded customer satisfaction also significantly affect the company’s Image and switching barrier.